Heat and mass transfer in the decomposition of calcium carabonate - Paulin, Andrej (Imperial College London, 1968)
The decomposition of single sintered calcium carbonate pellets of different porosities and the decomposition of packed beds of pellets has been investigated. A. thermobalance, modified to allow the simultaneous measurement of the temperature and weight of a decomposing sample was used for the single pellets investigation. It has been shown that the mechanism governing the decomposition reaction is independent of the pellet's porosity up to porosities of 70 %. According to this mechanism the rate of the reaction is controlled by heat and mass transfer. Thus the thermal conductivity of the porous lime and the effective CO2 diffusion coefficients through it are important parameters in the reaction model, and their values were measured in independent experiments, and compared with the values calculated from the decomposition experiments. The excellent agreement between the two sets of results, and the accuracy with which the model predicts measured reaction rates, confirmed the validity of the proposed reaction mechanism.